Respons Pertumbuhan dan Serapan N Tanaman Kedelai (Glycine max L. Merrill) dengan Pemberian Bradyrhizobium sp. dan Kapur di Tanah Mineral Masam - Irda Nila Selvia (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Sumatera Utara, 2022)
People's purchasing power for animal protein has decreased and has shifted to processed soy foods as one of the foods containing vegetable protein during the Covid-19 pandemic due to the economic recession. Soybeans are a source of high vegetable protein so they require a lot of Nitrogen (N). To fulfill the demand for soybeans, soybean cultivation can be carried out in acidic mineral soils with a low pH. Acidic mineral soil with a low pH causes it difficult for N nutrients to be available and the bacteria Bradyrhizobium sp. difficult to symbiosis with soybean plants. The aim of this study was to increase the growth and N uptake of soybean plants on acid mineral soils by inoculating Bradyrhizobium sp. and lime. The research was conducted in Jati Kesuma Village, Namorambe, Deli Serdang on a plot size 200 x 200 cm using a factorial randomized block design (RAK) with 2 factors. The first factor was the inoculating of Bradyrhizobium sp inoculants consisting of without inoculant; BGR 3 inoculant; and LP 3 inoculant. The second factor was liming consisting of without liming and liming with a dose of 1.06 kg/plot (pH 4.9 to 5.5). The results showed that Bradyrhizobium sp. BGR 3 inoculant tended to increase soybean plant height on acid mineral soil, but LP 3 inoculant was able to increase shoot root ratio and tended to increase N uptake 62.86% on acid mineral soil. The addition of lime was able to increase the growth of soybean plants on acidic mineral soil and increased N uptake 4.08%. The combination of LP 3 inoculant and without liming was able to increase shoot root ratio of soybean 133,33% on acid mineral soils.